2021
DOI: 10.1111/ajt.16333
|View full text |Cite
|
Sign up to set email alerts
|

T cell repertoire analysis suggests a prominent bystander response in human cardiac allograft vasculopathy

Abstract: T cells are implicated in the pathogenesis of cardiac allograft vasculopathy (CAV), yet their clonality, specificity, and function are incompletely defined. Here we used T cell receptor β chain (TCRB) sequencing to study the T cell repertoire in the coronary artery, endomyocardium, and peripheral blood at the time of retransplant in four cases of CAV and compared it to the immunoglobulin heavy chain variable region (IGHV) repertoire from the same samples. High‐dimensional flow cytometry coupled with single‐cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 25 publications
(37 reference statements)
1
15
0
Order By: Relevance
“…In myeloma patients, this was accompanied by augmented CD8+ T effector memory responses with enhanced IFNγ secretion in response to viral antigens ( 158 ). Given the potential role of heterologous immunity and/or bystander T-cells in rejection, this latter finding is also noteworthy ( 28 , 159 ). Interestingly, both of the aforementioned cases showed signs of TCMR on follow up biopsies consistent with the findings in a non-human primate model ( 155 – 157 ).…”
Section: Current Approaches To Desensitization In Heart Transplantationmentioning
confidence: 90%
“…In myeloma patients, this was accompanied by augmented CD8+ T effector memory responses with enhanced IFNγ secretion in response to viral antigens ( 158 ). Given the potential role of heterologous immunity and/or bystander T-cells in rejection, this latter finding is also noteworthy ( 28 , 159 ). Interestingly, both of the aforementioned cases showed signs of TCMR on follow up biopsies consistent with the findings in a non-human primate model ( 155 – 157 ).…”
Section: Current Approaches To Desensitization In Heart Transplantationmentioning
confidence: 90%
“…At minimum, columns are required for CD4 baseline unstimulated repertoire, CD4 antigen-stimulated repertoire, CD8 baseline unstimulated repertoire, CD8 antigen-stimulated repertoire, and at least one post-transplant blood or biopsy specimen (use biopsy as a demonstrative example in following text, figure and table). The data matrix format is provided as standard output from Adaptive Biotechnologies' ImmunoSeq platform, which is utilized by our lab and many other groups for TCR-Sequencing [1][2][3][4][5][6][7][8], and we therefore take this as input for downstream analysis.…”
Section: Software Methodologymentioning
confidence: 99%
“…Our method and R script [11] have been extensively used by us [1][2][3][4][5][6] and others [7,8] in multiple types of human SOT studies, including intestine [2,5,6], liver [4], heart [7], kidney [8] and combined kidney and bone marrow transplants [1]. Our platform allows the integration of T cell clonotype, alloreactivity and RNA profiling on the single cell level to relate T cell functional profiles with clonotypes of individual T cells [6].…”
Section: Application and Summarymentioning
confidence: 99%
See 1 more Smart Citation
“…Utilization of scRNAseq not only enables the transcriptomic description of these cells responsible for rejection, but also provides the opportunity to study the allospecificity and track T and B cell clonal dynamics. Studies of cardiac cellular rejection have shown that graft infiltrating T cells overlapped with those found in the peripheral blood, but interestingly, there was minimal overlap of the B cells between the two compartments ( 112 ). The authors used this data to suggest that there is B cell clonal expansion in the allograft, which could occur as part of a well-known phenomenon of germinal center-like structures present in chronically rejecting allografts ( 113 , 114 ).…”
Section: Single Cell Rna Sequencingmentioning
confidence: 99%